A Fasciclin 2 morphogenetic switch organizes epithelial cell cluster polarity and motility. - Szafranski, P.; Goode, S. (Development, 2004)
Little is known about how intercellular communication is regulated in epithelial cell clusters to control delamination and migration. We investigate this problem using Drosophila border cells as a model. We find that just preceding cell cluster delamination, expression of transmembrane immunoglobulin superfamily member, Fasciclin 2, is lost in outer border cells, but not in inner polar cells of the cluster. Loss of Fasciclin 2 expression in outer border cells permits a switch in Fasciclin 2 polarity in the inner polar cells. This polarity switch, which is organized in collaboration with neoplastic tumor suppressors Discs large and Lethal-giant-larvae, directs cluster asymmetry essential for timing delamination from the epithelium. Fas2-mediated communication between polar and border cells maintains localization of Discs large and Lethal-giant-larvae in border cells to inhibit the rate of cluster migration. These findings are the first to show how a switch in cell adhesion molecule polarity regulates asymmetry and delamination of an epithelial cell cluster. The finding that Discs large and Lethal-giant-larvae inhibit the rate of normal cell cluster movement suggests that their loss in metastatic tumors may directly contribute to tumor motility. Furthermore, our results provide novel insight into the intimate link between epithelial polarity and acquisition of motile polarity that has important implications for development of invasive carcinomas.